Evaluation and Comparison of Acoustic Performance and Thermal Conductivity of Spacer Fabrics (Journal of Fiber Bioengineering and Informatics, 2018)
The utilization of 3-Dimensional (3D) porous textile materials by the civil and mechanical engineers for\rimproved thermo-acoustic environment has widened the research scope. Unconventional three-dimensional\rtextile material which grabs the attention of the researchers for multi-functional applications is spacer\rfabrics. Since spacer fabrics have superior thermal and acoustic characteristics compared to conventional\rwoven/knitted structures or nonwovens due to their wonderful 3D porous nature. It has two outer layer\rconnected with the help of monofilament or multifilament spacer yarn which kept the fabric bulkier\rwith low density and highly breathable. Due to porous nature, interconnected pores, bulkier and 3D\rstructure, the spacer fabrics have ability to attenuate more sound energy than the conventional materials.\rThis research paper presents an experimental investigation on the sound absorption behaviour and\rthermal properties of warp knitted spacer fabrics. The Sound absorption coefficient (SAC) and thermal\rconductivity (K) were measured using two microphone impedance tube and Alambeta. This study deeply\rdiscusses the influence of material parameters and characteristics on acoustic properties of 3D spacer\rknitted fabrics. The results show that the fabric surface property, porosity, flow resistivity and tortuosity\rhave significant effects on the sound absorption as well as thermal conductivity. With the obtained\rresults, this work derives regression equations and correlation between noise absorption and thermal\rproperties of spacer fabrics.
Keywords: Noise Reduction Coefficient (NRC); 3D Spacer Fabrics; Flow Resistivity; Thermal Conductivity